Diagnosis and treatment of pancreatic duct disruption or disconnection: an international expert survey and case vignette study. Issue 8 (August 2021) - Boxhoorn, Lotte; Timmerhuis, Hester C.; Verdonk, Robert C.; Besselink, Marc G.; Bollen, Thomas L.; Bruno, Marco J.; Elmunzer, B. Joseph; Fockens, Paul; Horvath, Karen D.; van Santvoort, Hjalmar C.; Voermans, Rogier P.; ,; et al.
Abstract: Background: Pancreatic duct disruption or disconnection is a potentially severe complication of necrotizing pancreatitis. With no existing treatment guidelines, it is unclear whether there is any consensus among experts in clinical practice. We evaluated current expert opinion regarding the diagnosis and treatment of pancreatic duct disruption and disconnection in an international case vignette study. Methods: An online case vignette survey was sent to 110 international expert pancreatologists. Expert selection was based on publications in the last 5 years and/or participation in development of IAP/APA and ESGE guidelines on acute pancreatitis. Consensus was defined as agreement by at least 75% of the experts. Results: The response rate was 51% ( n = 56). Forty-four experts (79%) obtained a MRI/MRCP and 52 experts (93%) measured amylase levels in percutaneous drain fluid to evaluate pancreatic duct integrity. The majority of experts favored endoscopic transluminal drainage for infected (peri)pancreatic necrosis and pancreatic duct disruption (84%, n = 45) or disconnection (88%, n = 43). Consensus was lacking regarding the treatment of patients with persistent percutaneous drain production, and with persistent sterile necrosis. Conclusion: This international survey of experts demonstrates that there are many areas for which no consensus existed, providing clear focus for future investigation.